(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Bone age assessment is a method for evaluating the level of skeletal maturity to estimate the actual age of a person. The aim of our study was to evaluate the relationship between the chronological age and degree of epiphyseal fusion of medial end of clavicle in population of Chhattisgarh (Central India) and to compare our results with the results of similar studies. The study was carried out in 100 healthy subjects (40 girls & 60 boys) aging from 16 to 25 years. The obtained results from the radiographs revealed that the complete fusion of epiphysis of medial end of clavicle is seen at 21-25 years. Females were consistently developing epiphyseal union at a younger age than their male counterparts. Results also suggest that the age of epiphyseal union is found to vary greatly indicating the need for separate standards of age of epiphyseal union for separate regions.